Children and Competence to Consent: Gillick Guiding Medical Treatment in New Zealand - McLean, Kathryn (Victoria University of Wellington Law Review, 2000)
The House of Lords’ decision of Gillick was delivered in 1985. The Court held that children who are under 16 years, but have the intelligence and understanding to be competent to give consent to a particular treatment, may give consent for themselves. To date New Zealand’s Parliament and courts have not adopted Gillick. The competence principle from Gillick has nonetheless gained a degree of acceptance in New Zealand medical and legal circles. This paper discusses the status of Gillick in New Zealand. It also analyses the majority judgments in Gillick to ascertain the exact principle that should be extracted from the decision. The main focus of this paper is to consider the application of the Gillick competence principle in the New Zealand context. In researching this paper, the author undertook four interviews with various New Zealand doctors to ascertain their practices and views of Gillick. This paper examines the questions of: who should assess Gillick competence; when it is appropriate to invoke the Gillick principle; and the issues involved in how a doctor could assess Gillick competence. Practical guidance is offered through a proposed set of guidelines for assessing Gillick competence which are appended to this paper.